Salammbô et la crise du personnage - Walid Ezzine (Flaubert: Revue Critique et Génétique)
In Salammbô, the report of the characters in objects is not only the sign of a new vision of the history, but also a particular conception of the heroism. The ascendancy of the character promoted and developed by a long romantic tradition is questioned in this novel by the exuberance of objects. Threatened by these, the characters become themselves objects and lose any initiative and any influence on the nature.